Regulatory Variables and Statutory Interpretation - William N. Eskridge Jr.; Judith N. Levi (Washington University Law Quarterly, 1995)
In this Article, we shall use the hypothetical as the means to describe the intellectual puzzle that separates the two disciplines, specify and develop our idea of words or phrases as "regulatory variables," and suggest larger implications of our concept.
Keywords: Linguistics; Law -- Interpretation & construction